HUBUNGAN PERILAKU SELF-CONTROL KARYAWAN DENGAN KEPUTUSAN PEMBELIAN PRODUK FAST FASHION - Nisa Syahidah, Izzatun; Noerharyono, Muchamad; Suryawati, Suryawati (Practice of Fashion and Textile Education Journal, 2023)
The purpose of this study was to determine the relationship between employee self- control behavior and the purchase decision of fast fashion products. This research method uses a survey method with a quantitative approach. The sample in this study was 100 respondents using a purposive sampling technique with questionnaires distributed online. Data analysis technique uses Pearson Correlation. The results of this study indicate that the categorization data on employee self-control behavior variables have high self-control (87%); the purchase decision variable shows that employees have a good fast fashion product purchase decision (100%) with no bad category; and after the Pearson Correlation test was carried out, the data results obtained a correlation coefficient value of 0.274 > 0.05 (H0 was accepted and H1 was rejected) In the result of the Pearson Correlation it was found that there was no relationship between employee self-control behavior and the decision to purchase fast fashion products. The level of correlation in this study is very low because the correlation coefficient is 0.110.